Minimally invasive zadek osteotomy: A cadaveric study of structures at risk - Anthony Schwab, DPM, MS; Corine L. Creech, DPM, FACFAS (Foot & Ankle Surgery: Techniques, Reports & Cases)
Minimally invasive surgery (MIS) has continued to expand with respect to applications throughout the forefoot and into the hindfoot. Our center has performed the minimally invasive Zadek osteotomy in ten fresh frozen cadaver limbs through a single percutaneous incision. Distances in millimeters (mm) were measured from the anterior and posterior arm of the osteotomy to identify nearby anatomical structures. We documented the position of the peroneal sheath and sural nerve relative to the lateral portal, and the position of the tibialis posterior tendon (TP), flexor digitorum longus tendon (FDL), posterior tibial artery (PTA), posterior tibial vein (PTV), and flexor hallucis longus (FHL). The average distance of the sural nerve and the peroneal sheath from the anterior and posterior aspect of the osteotomy about the lateral portal was 6.65, 11.21 and 21.84, 23.26 mm, respectively. No medial neurovascular or tendinous structure was damaged as a result of the osteotomy, and the closest medial structure at risk was the tibial nerve at an average of 24.51 mm from the anterior arm of the osteotomy and 18.21 mm from the posterior arm of the osteotomy. While several technique guides have been discussed, to our knowledge this is the first study looking into structures at risk for this specific procedure with previously established anatomic portals.Level of clinical evidence: Level V Cadaveric Study